Multifactorial determinants of cervical cancer treatment success - Tutik Rahayu; Yuni Sufyanti Arief; Mira Triharini; Chong Mei Chan; Sri Wahyuni; Intan Rismatul Azizah; Apriliani Yulianti Wuriningsih; Hernandia Distinarista; Maria Silveira de Jesus (Universitas Airlangga, 2026)
Introduction: The success of cervical cancer treatment is not solely determined by medical procedures but is also influenced by individual and external factors such as patient knowledge, family support, peer group involvement, and the role of health professionals. These factors enhance treatment adherence and patient participation during therapy. Objective: This study aimed to analyze the multifactorial roles of individual and external factors in the success of cervical cancer treatment. Methods: A quantitative, cross-sectional study was conducted in 2024 at XX General Hospital, Semarang, involving 135 cervical cancer patients. Data were collected from the cervical cancer patients using a validated and authorized questionnaire; independent variables included knowledge, family support, peer groups, and health professionals. The dependent variable was treatment success, defined as patients receiving at least one session of cancer treatment, including chemotherapy, surgery, radiotherapy, or chemoradiation, measured through self-reported confirmation of treatment received. Data were analyzed through univariate, bivariate (Somers'd test), and multivariate analyses using ordinal logistic regression. Results: Most patients had good knowledge (58.5%), good family support (57%), strong peer group support (58.5%), and adequate support from health professionals (53.3%). A total of 58.3% of respondents reported high treatment success. Bivariate analysis revealed strong, statistically significant associations between each independent variable and treatment success (P-value<.001; r=.881–.968). Multivariate analysis indicated that the four variables simultaneously influenced 81.5% of treatment success variation (R² = .815). Conclusion: Knowledge, family involvement, peer support, and health services, particularly by nurses, significantly contribute to the success of cervical cancer treatment in women. Integrating educational and social support interventions is essential for improving treatment outcomes, as these interventions enhance patients' adherence to therapy, promote self management, reduce treatment-related anxiety, and facilitate the early detection of complications, ultimately leading to better quality of life and overall treatment effectiveness. Keywords: cervical cancer; family support; knowledge; peer group